2013
DOI: 10.1016/j.toxicon.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Crotalus durissus terrificus venom on chronic edema induced by injection of bacillus Calmette-Guérin into the footpad of mice

Abstract: In this study, we evaluated the effect of the Crotalus durissus terrificus (Cdt) venom on the chronic paw edema induced by the injection of bacillus Calmette-Guérin (BCG) into the footpad of mice. The BCG injection evoked chronic edema, which was significantly diminished in animals treated subcutaneously (s.c.) with Cdt venom 1 h before or after the BCG injection. This inhibition persisted throughout the evaluation period (15 days). In mice injected with Cdt venom 6 or 11 days after injection of BCG, we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…To our knowledge, this is the first demonstration that LDs induced by a group IIA sPLA 2 are equipped with a COX-1 enzymatic system and are involved in synthesis of a lipid mediator implicated in inflammatory resolution, such as 15-d-PGJ 2 . In addition, it should be noted that release of the anti-inflammatory mediator 15-d-PGJ 2 is in line with the immunomodulatory effects of CB and sheds new light on the mechanisms by which whole Crotalus snake venom and CB, its major sPLA 2 , can reduce or abolish inflammatory events 5, 68 .…”
Section: Discussionmentioning
confidence: 76%
“…To our knowledge, this is the first demonstration that LDs induced by a group IIA sPLA 2 are equipped with a COX-1 enzymatic system and are involved in synthesis of a lipid mediator implicated in inflammatory resolution, such as 15-d-PGJ 2 . In addition, it should be noted that release of the anti-inflammatory mediator 15-d-PGJ 2 is in line with the immunomodulatory effects of CB and sheds new light on the mechanisms by which whole Crotalus snake venom and CB, its major sPLA 2 , can reduce or abolish inflammatory events 5, 68 .…”
Section: Discussionmentioning
confidence: 76%
“…It was also shown that LXA 4 was involved in the inhibitory effect of CTX on the phagocytic activity of macrophages in vitro [ 49 ]. Furthermore, LXA 4 induced by CTX can be correlated with the inhibition of neutrophil migration to the peritoneal cavity induced by carrageenan injection or paw edema in mice injected with Bacillus Calmette-Guérin (BCG) [ 50 , 97 ]. In accordance with these reports, our data suggest that CTX induces an anti-inflammatory status in mice able to control the intestinal inflammation induced by the TNBS.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumoral effects of CTX have also been reported in patients with lung and mammary carcinoma [ 8 ]. Evidence has been accumulated that CTX presents inhibitory effects on inflammatory response [ 13 , 14 ]. Inflammation is closely associated with cancer growth [ 15 ].…”
Section: Introductionmentioning
confidence: 99%